2019
DOI: 10.1155/2019/3579671
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Technical Characteristics of Coronary Angiography and Percutaneous Coronary Interventions Performed before and after Transcatheter Aortic Valve Replacement with a Balloon-Expandable Valve

Abstract: Objectives. To report on the feasibility and technical differences between coronary procedures performed before and after TAVR with the balloon-expandable Edwards-SAPIEN or the SAPIEN XT valves. Background. Coronary artery disease (CAD) and aortic stenosis often coexist. Transcatheter aortic valve replacement (TAVR) is emerging as a treatment for younger and lower surgical risk patients who might not present with clinically evident CAD before TAVR. The demand for performing post-TAVR coronary angiograms (CAs) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 29 publications
1
13
0
Order By: Relevance
“…It depends mainly on individual application settings. Thus, algorithms developed to support diagnostic angiography, performed with the aim of subsequent emergent blood flow restoration, should correspond to the following requirements: input video frame rate of 7.5–15 frames per second 40 , 41 , the duration of the procedure less than 25 min, and individual preferences of the operator 36 . We concluded that neural network architectures with an inference time of less than 66 ms are suitable for this task (Table 4 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It depends mainly on individual application settings. Thus, algorithms developed to support diagnostic angiography, performed with the aim of subsequent emergent blood flow restoration, should correspond to the following requirements: input video frame rate of 7.5–15 frames per second 40 , 41 , the duration of the procedure less than 25 min, and individual preferences of the operator 36 . We concluded that neural network architectures with an inference time of less than 66 ms are suitable for this task (Table 4 .…”
Section: Discussionmentioning
confidence: 99%
“…Two evaluation metrics were used to compare the performance of the selected neural networks. Precision, Recall, and F1-score were used to compare the classifiers and the mAP metric was used to judge object localization 36 . For mAP a predefined threshold value for Intersection over Union equal to 0.5 was used.…”
Section: Methodsmentioning
confidence: 99%
“…The feasibility of accessing the coronary ostia and performing PCI after implantation of balloon-expandable THVs (SAPIEN™, Edwards, Irvine, California, USA) has been shown in several observational studies ( 33 , 37 , 38 ). In general, coronary cannulation in patients with balloon-expandable valves is technically less challenging than with self-expanding valves, mainly due to the lower stent frame that in most cases does not protrude over the coronary orifice.…”
Section: Balloon-expandable Transcatheter Heart Valvesmentioning
confidence: 99%
“…Notably, 10% of patients underwent CA (with or without PCI) after TAVI, and no differences in CA performance and/or PCI results in relation to valve position were found. Ferreira-Neto et al compared the feasibility and success rate in 41 patients with balloon-expandable valves (SAPIEN™ and SAPIEN XT™) who underwent CA and/or PCI before and after TAVI during a mean follow-up period of 2 years ( 38 ). Independent of the position of the valve (in the PCI group, 23% at the supra-ostial and 38.5% at the ostial or infra-ostial level), no differences in terms of procedural factors including arterial access site, number and choice of catheters, procedural duration, fluoroscopy time, contrast agent volume, and successful selective coronary injection were found between pre- and post-TAVI CA ( 38 ).…”
Section: Balloon-expandable Transcatheter Heart Valvesmentioning
confidence: 99%
“…It depends mainly on individual application settings. Thus, algorithms developed to support diagnostic angiography, performed with the aim of subsequent emergent blood ow restoration, should correspond to the following requirements: input video frame rate of 7.5-15 frames per second 39,40 , the duration of the procedure less than 25 minutes, and individual preferences of the operator 41 . We concluded that neural network architectures with an inference time of less than 66 milliseconds are suitable for this task (Table 4.…”
Section: Image Processing Speedmentioning
confidence: 99%